Preliminary exploration of vacuum impregnation as a method for iron and vitamin B1 fortification of white rice (Oryza sativa) - Pueblos, Ne P.; Francisco, Maria Leonora Lotis dL. (Quezon City University of the Philippines Diliman, 2025)
This study explored vacuum impregnation (VI) to fortify white rice (Oryza sativa) with iron and Vitamin B1. Iron was supplied in the form of ferrous gluconate (FeGLU), while Vitamin B1 was provided as thiamine hydrochloride (ThCIHCl). The rice samples used were of the Dinorado Mindoro variety, sourced from a local seller in Caloocan City, Metro Manila. Twenty-five grams of rice were immersed in a nutrient solution prepared by mixing separate 10% solutions of FeGLU and ThCIHCl. VI was conducted using a desiccator jar connected to a vacuum pump, applying pressures of 0, 300, and 500 mmHg below atmospheric pressure (resulting in approximate absolute pressures of 760, 460, and 260 mmHg, respectively). Following VI, the rice samples were dried at 45°C for 12 hours and analyzed for color and nutrient uptake. The fortification process significantly altered the color of the rice, changing it from white to a dark yellowish-green hue. Spectrophotometric analysis showed FeGLU uptake rates of 52.07% and 98.38% for the 0 and -300 mmHg treatments, respectively. However, ThCIHCI data were deemed unreliable due to significant overestimation, attributed to limitations in the analytical method. These findings suggest that VI is a promising technique for iron fortification of white rice. However, further research is needed to establish a reliable method for Vitamin B1 quantification and to assess the potential of VI for multi-nutrient fortification.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Rice -- processing; Food -- analysis; Rice -- Philippines